(untitled) (Research, Society and Development, 2021)
The present article discusses the potential of using the Virtual Teaching-Learning Environment (AVEA) Moodle as a tool to support the management of scholarships at the Open University of Brazil (UAB), inserted at the Federal University of Santa Maria (UFSM), which is managed by the Educational Technology Center (NTE). The work was developed under a qualitative research approach, in a case study context. The target audience was the general coordinators (22) and the tutoring coordinators (05) of the courses at UAB / UFSM. As a data collection instrument, a questionnaire was adopted, with 21 open and closed questions. The revealed data show the potential of using Moodle in the mediation of the scholarship system and the implementation of a tutorial that helps the coordinators in the management of scholarship payment. It is an important tool that makes the process more agile and without so many bureaucratic obstacles. The use of AVA Moodle makes the process more fluid, democratic and transparent.